Negotiating Academic Authority and Cultural Values in Minangkabau Thesis Seminars: A Critical Discourse Analysis - Saiyidinal Firdaus (Essence: Journal of English Language Teaching, Linguistics, and Literature, 2026)
This study investigates how academic authority and cultural values are negotiated in thesis seminar practices within Minangkabau higher education, addressing a critical gap in critical discourse analysis (CDA) concerning the integration of institutional power and local cultural norms. While previous studies have predominantly conceptualized academic discourse as structurally hierarchical, limited attention has been given to how such authority is dynamically mediated by culturally embedded communicative practices. Employing a qualitative design grounded in CDA, this study analyzes approximately 24 hours of video-recorded thesis seminar interactions involving lecturers and undergraduate students. The data were examined using Fairclough’s three-dimensional framework, focusing on textual, interactional, and socio-cultural levels of analysis. The findings reveal four dominant discursive strategies of authority negotiation: directive authority enactment, mitigated authority negotiation, collaborative alignment, and culturally indexed deference. These strategies demonstrate that authority is not only exercised through direct control but also negotiated through politeness, interactional alignment, and culturally shaped deference. Based on these patterns, the study proposes the Hybrid Authority Negotiation Model (HANM), which conceptualizes authority as a dynamic interplay between institutional and cultural dimensions. The study concludes that academic discourse in thesis seminars is hybrid, context-dependent, and culturally mediated rather than purely hierarchical. The findings contribute theoretically by extending CDA toward a more culturally responsive framework and practically by informing more context-sensitive academic communication practices in higher education. This research highlights the importance of integrating cultural perspectives into discourse analysis and pedagogical design in increasingly globalized academic environments.